Prevalence of cancer among the urban and rural community of Surendranagar district, Gujarat - Patel, Nitesh M.; Jasani, Pratik K.; Kartha, Girija P.; Patel, Sweta N. (International Journal Of Community Medicine And Public Health, 2019)
Background: Non-communicable diseases (NCDs) are mainly cardiovascular diseases, cancers, chronic respiratory diseases and diabetes-are the world’s biggest killers. In developing countries, cancer is among the ten most common causes of mortality. Cancer is not just one disease but many diseases. There are more than 100 different types of cancer. The most conspicuous feature of the distribution of cancers between the sexes is the male predominance of lung cancer. Prostate, colorectal, stomach and liver cancer are also much more common in males. Cancer of breast, colorectal, cervix, uteri, lung and stomach are common in females. This study was conducted to identify the prevalence of various types of cancers in rural and urban community of Surendranagar district. Methods: It was a cross-sectional study carried out among 300 rural and 300 urban families selected by simple random sampling. Data was collected and analysed by Statistical Package for Social Sciences and Microsoft Excel have been used to generate graphs, tables, etc. Results: Study revealed that out of total study population (2053), 37 participants were having cancer. The prevalence of cancer was 1.80% in our study. Out of 37 respondents who were having cancer, majority cases were oral cancer 11 (29.73%) and 9 (24.32%) lung cancer, followed by cancer breast 5 (13.51%), cancer colorectal 5 (13.51%) and other cancers 7 (18.92%). Conclusions: Prevalence of cancer was increasing with the age. Higher number of cancer cases was found amongst older age than younger age. Significant difference was found between cancer prevalence and gender.